Enrichment and domestication of a microbial consortium for degrading aniline. (August 2021) - Chen, Hui; Sun, Chongran; Liu, Ronghui; Yuan, Mingzhu; Mao, Zhenhua; Wang, Qi; Zhou, Hongbo; Cheng, Haina; Zhan, Wenhao; Wang, Yuguang
Graphical abstract: Highlights: A microbial consortium was obtained to degrade aniline effectively. Comamonas and Zoogloea accounted for the efficient removal of aniline. The microbial consortium had a wide adaptability to environmental stresses. Abstract: In this study, a microbial consortium was enriched and acclimated to degrade aniline by the aerobic bioreactor. The system achieved a high degradation efficiency of aniline (over 99%) within a short period. Meanwhile, the removal rate of NH4 + -N was up to 33.3%. The dominant populations of Comamonas and Zoogloea were critical for maintaining the removal performance. Ortho-cleavage and meta-cleavage pathways were responsible for degrading aniline. Our work presented that the microbial consortium could effectively treat aniline, and provided a potential alternative for eliminating aniline.